SURGICAL METHODS OF OBESITY TREATMENTS FOR LOWERING BODY MASS INDEX - Barno Kh. Shagazatova; Oktyabr R. Teshaev; Nasiba A. Kudratova; Umid S. Ruziev (Central Asian Journal of Medicine, 2022)
Introduction. In connection with the upward trend in the number of obese people, new approaches to the treatment of obesity are being explored. Surgical methods of treating severe obesity have become widely used throughout the world in recent decades. The main task of such methods is to influence the course of diseases associated with obesity (bariatric surgery) by means of a significant decrease in body mass. Material and methods. We studied 72 obese patients who were divided into 2 groups depending on the degree of obesity. In each group, in order to reduce body weight, 3 types of surgical interventions were performed (drain resection, gastric bypass, mini-gastric bypass) taking into account BMI, age, the presence of disorders of carbohydrate metabolism, as well as concomitant pathology. Patient inclusion criteria: patients with II-III degree of obesity, with no persistent decrease in body weight on the background of diet, exercise and drug treatment. All patients underwent BMI (weight in kg divided by the square of the height in meters) and waist measurements. Results. The largest percentage in the decrease in BMI was in gastric bypass and mini-gastric bypass by 33% and 35%, respectively, in women and 32.7% and 32%, respectively, in men. Draining resection showed the lowest percentage of BMI reductions in women and men at 24% and 18.3%, respectively. The decrease in BMI and WM significantly exceeded in the group of patients with III degree of obesity, so the level of BMI decreased by 22.8% in the group with II degree, and by 30% in the group with III degree of obesity. Decrease in WM 20% and 22% respectively. Conclusion. Decrease in BMI was achieved with the use of all types of surgical interventions for obesity treatment. But the most persistent weight loss was observed with gastric bypass and mini-gastric bypass. A significant decrease in BMI and WM after surgical treatment was observed in patients with grade III obesity, which is probably associated with a relatively large initial overweight and the most frequently performed type of surgery in this group - gastric bypass and mini-gastric.